2021
DOI: 10.3390/toxins13120856
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Smectite-Based Mycotoxin Binder in Reducing Aflatoxin B1 Toxicity on Performance, Health and Histopathology of Broiler Chickens

Abstract: The aim of the experiment was to investigate the efficacy of a smectite-based clay binder (Toxo-MX) in reducing the toxicological effects of aflatoxin B1 (AFB1) in commercial broiler chickens. A total of 450 one-day old male broiler chickens were randomly allocated into three treatment groups with ten replicates of 15 birds each in a 42-day feeding experiment. The dietary treatments included a negative control (NC, a basal diet with no AFB1 and binder), a positive control (PC, a basal diet contaminated with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Furthermore, feeding AFB1 to the PC group significantly reduced the contents of serum TP, ALB, and GLU, which is in agreement with the results of Bagherzadeh Kasmani et al [50] and Chen et al [51]. The toxicity of AFB1 has been demonstrated to trigger the suppression of hepatic protein, carbohydrate, and lipid metabolism, and might therefore lead to liver enlargement and serum biochemical changes [37,52]. The present study showed that serum GOT and GPT concentrations and residual levels of AFB1 were significantly elevated in broilers fed with the AFB1-contaminated diet.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, feeding AFB1 to the PC group significantly reduced the contents of serum TP, ALB, and GLU, which is in agreement with the results of Bagherzadeh Kasmani et al [50] and Chen et al [51]. The toxicity of AFB1 has been demonstrated to trigger the suppression of hepatic protein, carbohydrate, and lipid metabolism, and might therefore lead to liver enlargement and serum biochemical changes [37,52]. The present study showed that serum GOT and GPT concentrations and residual levels of AFB1 were significantly elevated in broilers fed with the AFB1-contaminated diet.…”
Section: Discussionsupporting
confidence: 87%
“…Salem et al have reported renal congestion, vacuolization and tubular epithelial necrosis in chicks fed 0.25 ppm AFB1 [ 41 ]. Likewise, the main histopathological changes in the kidney of birds exposed to 0.5 ppm AFB1 including focal infiltration of inflammatory cells and glomerular atrophy were reported by Zabiulla et al [ 42 ]. Weight loss is a marker of poisoning [ 43 ], and these nephrotoxic changes were also reflected in mice growth characteristics, as manifested by reduced body weight and kidney coefficients.…”
Section: Discussionmentioning
confidence: 69%
“…4 In other studies, liver alterations were also observed even after addition of mycotoxin binders in contaminated diets, although a reduced magnitude and severity characterized by degeneration rather than necrosis were noted. 51,52 Neef et al 20 also observed that supplementing 0.5% HSCA to diets contaminated with AFB1 at high levels of 2,500 μg/kg did not prevent ultrastructural changes in livers of broiler chickens fed the contaminated diet from hatch to 21 d of age, indicating that at very high AFB1 levels, 0.5% HSCA failed to protect the birds.…”
Section: ■ Discussionmentioning
confidence: 99%